Concepts of Work: from Traditional Social-Labor Ideas to Modern Effects of Digital Transformation - Zs. Riczu; G. Melypataki; D. A. Mate (Journal of Digital Technologies and Law, 2023)
Objective: technology and digitalization play a converse role in these two fields of study of criminal sciences. On the one hand, they are used by agencies of criminal justice system in order to control, manage and prevent crime and criminals. On the other hand, criminals enjoy technology in carrying out their plans to commit crime. Thus, from the criminal sciences’ perspective, technology may be used or misused, and this is an interesting topic, and at the same time, an important research area for criminologists.Methods: the present article seeks to provide a descriptive-analytical discussion about digitalization of criminology and criminal justice in the light of modern technologies, internet and cyberspace. It introduces new areas and sub-disciplines including administrative criminology based upon actuarial justice and risk management/assessment theory, cyber criminology and cyber victimology, as two sub-disciplines of the new century, and algorithmic or computational criminology, as one of the latest area in criminal sciences, which all are influenced by digitalization and technology.Results: authors concluded that due to the digitalization atypical work emerges but legislator defines the scope of work regulated by law and that makes atypical work relationship becomes a typical work relationship. At the same time some areas fall into the gray zone. To fix that legislator should provide an interpretation that will not become empty in a year or two due to technological changes.Scientiﬁc novelty: the applicability of technology and digitalization in criminology and criminal justice has widely increased and developed, specifically since the beginning of the third millennium.Practical signiﬁcance: digitalization and Technology has become increasingly important to criminology and criminal justice at both the theory and practice within the sphere of social and criminal sciences. The nature and types of crime and criminals, and also the methods and mechanisms of control and preventing them in the light of requirements of criminal policy and criminal justice are highly dependent upon technology and digitalization.